Influencing behavioral change by customer engagement amongst youth - Singh S (Dove Medical Press, 2011)
Sonal SinghMarketing and Management Department, Macquarie University, Sydney, New South Wales, AustraliaAbstract: It is widely accepted that many social and health problems have underlying behavioral causes. Because these problems are rooted in human behavior, solutions to deal with them also lie in human behavior. This paper examines ways of integrating customer engagement in social programs to influence and initiate behavior change effectively with a special focus on youth. This work followed a theoretical deduction by use of a literature review. Social marketing places emphasis on behavior change, and one of the key challenges for social marketers is to ensure a perceived value for customers in taking up and maintaining positive behavior. If perceptions, beliefs, attitudes, and values influence behavior, then the central focus should be on the youth. Integrating youth is a prerequisite for effective social marketing programs and ultimately behavioral change. This approach will pave the way for effective brand positioning and brand loyalty in social marketing which has been lacking and requires more attention from researchers and policymakers. This paper outlines theoretical developments in social marketing that will increase the effectiveness of social marketing programs overall. Existing social marketing literature typically focuses on social marketing interventions and behavioral change. This paper uses customer engagement within a social marketing context so that social marketing programs are perceived as brands to which youth can relate.Keywords: social marketing, customer engagement, behavioral influence, change, youth